Justifikasi Hukum Pidana terhadap Kebijakan Kriminalisasi Pelanggaran Hak Cipta, serta Perumusan Kualifikasi Yuridis dan Jenis Deliknya - Wibowo, Ari (Jurnal Hukum IUS QUIA IUSTUM, 2016)
This study focuses on a policy of criminalization of copyright infringement through Law No. 19 of 2002 on Copyright, as well as policy formulation on juridical qualification and the type of the offense. This research includes the study of normative law with legal materials obtained through document study or literature. From the analysis, it was concluded that the theory justiying criminalization of copyright infringement is a liberalindividualistic theory which is based on social harm, as well as a moral theory that makes morality as a parameter. Moreover, no judicial qualifications emphasized the offense, as well as the determination of the crime of copyright as an ordinary offense can lead to legal problems in practice.